Thalictrum kangdingense (Ranunculaceae), a new synonym of T. megalostigma from China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild from its type locality, we demonstrate that Thalictrum kangdingense, recently described from Kangding county in western Sichuan province, China, is readily distinguishable from T. xinningense by an array of morphological characters but is actually conspecific with T. megalostigma, a species with its type locality also in Kangding. We therefore reduce T. kangdingense to the synonymy of T. megalostigma herein. The morphological distinction between T. baicalense and T. megalostigma is also clarified.